Quantitative Ultrasound in Ex Vivo Fibrotic Rabbit Livers - Franceschini, Emilie; Escoffre, Jean-Michel; Novell, Anthony; Auboire, Laurent; Mendes, Vanda; Benane, Yanis M; Bouakaz, Ayache; Basset, Olivier (Ultrasound in medicine & biology, 2019)
Liver fibrosis is the common result of chronic liver disease. Diagnosis and grading liver fibrosis for patient management is mainly based on blood tests and hepatic puncture-biopsy, which is particularly invasive. Quantitative ultrasound (QUS) techniques provide insight into tissue microstructure and are based on the frequency-based analysis of the signals from biologic tissues. This study aims to quantify how spectral-based QUS parameters change with fibrosis grade. The changes in QUS parameters of healthy and fibrotic rabbit liver samples were investigated and were compared with the changes in liver stiffness, using shear wave elastography. Overall, the acoustic concentration was found to decrease with increasing fibrosis grade, and the effective scatterer size was found to be higher in fibrotic livers when compared with normal liver. The result of this study indicates that the combination of three QUS parameters (stiffness, effective scatterer size and acoustic concentration) provides the best classification performance, especially for classifying healthy and fibrotic livers.